A new species of the codlet genus Bregmaceros from the western Pacific Ocean (Gadiformes: Bregmacerotidae) - Ho, Hsuan-Ching; Endo, Hiromitsu; Chu, Tah-Wei (Zootaxa, 2020)
Bregmaceros retrodorsalis sp. nov., a new codlet species is described based on specimens from shallow to deep waters off Japan and Melanesia. It differs from all congeners by having the origin of second dorsal-fin well posterior, above bases of 5th to 7th anal-fin rays and combination of the following characters: a pointed snout distinctly longer than eye diameter; upper lobe of opercle branched distally; body relatively slender, its depth 10.0‒13.0% SL; 13 principal caudal-fin rays (middle 11 branched); 52‒57 second dorsal-fin rays; 58‒63 anal-fin rays; 16‒18 transverse scale rows below dorsal-fin origin; 86‒93 longitudinal scale rows along body axis; vertebrae 55‒58; entire body evenly covered with melanophores, those on lateral sides forming regular longitudinal rows, one melanophores per scale; head and isthmus entirely, but loosely, covered with variably sized melanophores.